2022
DOI: 10.1364/oe.455553
|View full text |Cite
|
Sign up to set email alerts
|

Percussion drilling in glasses and process dynamics with femtosecond laser GHz-bursts

Abstract: We report for the first time to our knowledge on top-down percussion drilling of high-quality deep holes in different glasses with femtosecond laser pulses in GHz-burst mode. We reveal the dynamics of the percussion drilling process by pump-probe shadowgraphy and thermal camera imaging demonstrating that the drilling process in GHz-burst mode is fundamentally different from single-pulse processing and confirming the presence of thermal accumulation. Moreover, we show a comparison to drilling by femtosecond sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…Furthermore, we noticed that detrimental extended cracks appear along the Bessel beam due to heat accumulation when the burst repetition rate is too high. A similar phenomenon has been observed in drilling experiments in the GHz-burst regime [ 47 ]. Indeed, in sodalime, for example, the burst repetition rate in the drilling experiments was limited to 10 kHz, while cutting with the Bessel beam is possible with repetition rates up to 20 kHz without HAZ appearing.…”
Section: Cutting Results and Discussionsupporting
confidence: 82%
“…Furthermore, we noticed that detrimental extended cracks appear along the Bessel beam due to heat accumulation when the burst repetition rate is too high. A similar phenomenon has been observed in drilling experiments in the GHz-burst regime [ 47 ]. Indeed, in sodalime, for example, the burst repetition rate in the drilling experiments was limited to 10 kHz, while cutting with the Bessel beam is possible with repetition rates up to 20 kHz without HAZ appearing.…”
Section: Cutting Results and Discussionsupporting
confidence: 82%
“…Other works have reported on combining MHz- and GHz-burst strategies in a biburst mode for ablation [ 31 , 32 ]. Very recently, we investigated the percussion drilling process in glasses [ 33 , 34 ] and in sapphire [ 34 ] in GHz-burst mode applying pump-probe shadowgraphy and thermal imaging [ 34 ]. Furthermore, we have shown that efficient drilling was even possible at fluences where the individual pulses within the burst have a fluence clearly lower than the ablation threshold of the material, which underlines that this processing mechanism profits from beneficial thermal accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…1 GHz intra-burst pulse repetition frequency with a Gaussian beam. 49,50 This approach allows for tuning the burst envelope as well as burst energy and duration. While the method can produce very high aspect ratio holes in different types of glass (∼30 µm diameter holes with 30:1 aspect ratio in soda lime glass and 70:1 in fused silica 51 ), the process requires tens of bursts to initiate drilling, a low inter-burst pulse repetition frequency to reduce thermal effects and sidewall collapse, and a very long drill time.…”
Section: Laser-based Methods For Forming Tgvsmentioning
confidence: 99%